IDENTITY CONCEPT OF SUMPINGAN KIWO IN WAYANG KRUCIL - Irawanto, Rudi; Sutarwiyasa, I Ketut (International Conference on Cultural Studies, 2019)
The aesthetic concept of “Nusantara” always puts everything with their respective spouses. The principle of opposition of the pair can be found in all aesthetic and ethical settings in “Nusantara”. Opposition partner pairs place the right status as the left pair, both as a bad pair, and also right as the wrong pair. The principle does not see good as opposed to ugliness, but as a partner that must be accommodated and arranged according to their respective portions. The principle of opposition of this pair can also be found in the chopper or the arrangement of wayang positions in Java. The wayang performance in Java always places a person who is considered bad or not good in the left position and a figure who is considered good in the right position. Right and left indicate the antagonistic and protagonist status in performance. In the wayang krucil chopsticks in East Java, the left figures are analogous as figures who oppose the concept of truth. Wayang krucil is a wooden puppet by taking the story of Babad Majapahit and the Babad Panji. In the story of the Babad Majapahit, the Kiwo sumpingan (left) shows figures who are considered to have rebellious nature and oppose royal policy. Figures of Klonosewandono, Menakjingo to Menakkoncar are positioned as left figures or bad figures. The placement of the left figure in this wayang krucil blowstick is interesting to study further, considering that in the present perspective the Banyuwangi community rejects the figure of Menak Jinggo as a bad characterist. The Klonosewandono figure was also rejected as a left figure by the Ponorogo community, remembering Prabu Klonosewandono as a core figure in the Ponogogo reog performance. The identity of the left and right chopsticks in wayang krucil can be seen as a classification of identity based on the legitimate perception of the Majapahit ruler at that time. Left and right in the Wayang Krucil chopsticks basically show the stigma given by the authorities to their political opponents using art media. Identity is built in the perception of power, so that it shows absolute good and bad positions.